(untitled) (TEL Tempo, Espaço e Linguagem, 2025)
Dona Xepa, which was originally a play (1953), become a film and a soap opera. The success of Dona Xepa on television was so great thet it warranted a remake. However, this article analyzes how the film Dona Xepa (1959) was created based on the play written by Pedro Bloch for the actress Alda Garrido and how the character that the actress created for herself, that of the caricature, influenced the production of the film. In the second parto in the article, the analysis focuses on gender.